Somatic symptom and related disorders in the Arab world: a narrative review of clinical features and care implications - Eid, Mario; Abi Kheir, Venise; Bizri, Maya; Larnaout, Amine; El Hayek, Samer (Frontiers in Psychiatry, 2025)
BackgroundSomatic symptom and related disorders (SSRDs) are prevalent worldwide, but their expression, help-seeking patterns, and management are strongly shaped by cultural context. In the Arab world, where mental health stigma and distinct explanatory models are common, SSRDs remain under-studied despite their clinical and public health significance.MethodsWe conducted a narrative review of 35 studies published through June 2025 on SSRDs in Arab populations. Searches of PubMed, Scopus, and Google Scholar identified observational studies, case reports, and cross-sectional surveys addressing Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR) SSRD categories.ResultsSomatic symptoms disorder (SSD) was the most frequently investigated disorder, with prevalence ranging from 12% to 46%. Across studies, female gender, low educational attainment, chronic medical comorbidity, and trauma history were consistent risk factors. Common symptoms included muscle, back, and abdominal pain, often accompanied by depression and anxiety. Illness anxiety disorder, functional neurological symptom disorder, and factitious disorders were less studied but carried important diagnostic, cultural, and service delivery challenges.ConclusionSSRDs are common but under-recognized in Arab contexts. Effective management requires early detection in primary care, culturally sensitive communication, and disorder-specific interventions. Future research should broaden the scope beyond SSD, examine longitudinal and trauma-related pathways, and evaluate culturally adapted models of care.